2014
DOI: 10.5539/jas.v6n11p247
|View full text |Cite
|
Sign up to set email alerts
|

Seed Protein and Starch Qualities of Drought Tolerant Pigeonpea and Native Tepary Beans

Abstract: Tepary bean and pigeonpea were highly drought tolerant food legumes and were profitable in arid regions with sustainable productivity. Protein and starch, major constituents of legume grain, were used in various forms for human and animal consumption. Therefore, present investigation was carried out with an objective to evaluate protein content and various factors influencing qualities of starch in pigeonpea and tepary bean. Significant differences (p < 0.05) were observed for protein and starch qualities amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
0
6
1
Order By: Relevance
“…According to Olagunju et al (2020), the composite flour displayed higher peak viscosity, trough viscosity as well as final viscosity at the increasing level of pigeon pea when compared to the whole wheat flour. Higher pasting characteristics of composite flour perhaps due to the low amylose content in the pigeon pea than the whole wheat flour (Narina et al, 2014). These results are opposite to the study executed by Wani et al (2016) for the preparation of Chapatti from the whole wheat flour fortified with different levels (5-20%) of a kidney bean and black gram flour.…”
Section: Dough Rheology Affected By Pulse Fortificationcontrasting
confidence: 57%
“…According to Olagunju et al (2020), the composite flour displayed higher peak viscosity, trough viscosity as well as final viscosity at the increasing level of pigeon pea when compared to the whole wheat flour. Higher pasting characteristics of composite flour perhaps due to the low amylose content in the pigeon pea than the whole wheat flour (Narina et al, 2014). These results are opposite to the study executed by Wani et al (2016) for the preparation of Chapatti from the whole wheat flour fortified with different levels (5-20%) of a kidney bean and black gram flour.…”
Section: Dough Rheology Affected By Pulse Fortificationcontrasting
confidence: 57%
“…Chinma et al (2012) also observed higher pasting properties for wheat–plantain–sesame composite flours. Higher pasting values observed in composite flours may be attributed to reduction in amylose content of the flours; the flour substitutes (acha and pigeon pea) generally have lower amylose content (18.7–19.8% and 7.76–12.31%, respectively) than WWF (Jideani et al , 1996; Narina et al , 2014).…”
Section: Resultsmentioning
confidence: 99%
“…As pigeonpea is known to be one of the drought tolerant crops among the grain legumes, identification of candidate genes for imparting drought tolerance will be useful across the legume crops (Narina et al, 2014 ). The analysis of the pigeonpea genome has identified 111 proteins which were homologous to drought-responsive universal stress proteins (Varshney et al, 2012a ).…”
Section: Genomic Resourcesmentioning
confidence: 99%